2020
DOI: 10.1057/s41599-020-00592-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of happiness among healthcare professionals between 2009 and 2019: a systematic review

Abstract: Happiness is characterized by experiencing positive emotions while simultaneously perceiving one’s life as meaningful and worthwhile. Research on the mental health of healthcare professionals usually focuses on psychopathology as opposed to the positive aspects of mental health. Thus, the purpose of this study is to examine recent literature on individual-level and organization-level determinants of healthcare professionals happiness. The EBSCOhost, PubMed, Scopus, and Web of Science databases were searched fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 47 publications
(115 reference statements)
1
39
0
4
Order By: Relevance
“…In comparison, there is a dearth of research on healthcare workers' positive mental health aspects such as happiness, especially in low-and middle-income countries 6,7 . To effectively develop and implement happiness policy among healthcare workers, empirical research is necessary 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, there is a dearth of research on healthcare workers' positive mental health aspects such as happiness, especially in low-and middle-income countries 6,7 . To effectively develop and implement happiness policy among healthcare workers, empirical research is necessary 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, healthcare workers are individuals trained to practice ethical and evidence-based medicine, and to provide quality health services 9 . Recently, an extensive systematic review on the determinants of healthcare professionals' happiness reported that there is currently no universal definition of happiness 8 . In this study, happiness is viewed as the main result of positive affect and an intrinsic feeling that one's life is purposeful and worth living 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative studies in the Kenya assessing healthcare workers’ happiness [ 14 ], health-related quality of life [ 15 ], and motivation [ 16 , 17 , 18 , 19 ] have also been published. In 2020, systematic reviews on healthcare workers happiness globally [ 20 ] and motivation in East Africa [ 21 ] were also published. These studies and reviews revealed an existing literature gap in healthcare workers’ experience of happiness, health, and motivation in the context of health systems, especially in the African region [ 15 , 16 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, systematic reviews on healthcare workers happiness globally [ 20 ] and motivation in East Africa [ 21 ] were also published. These studies and reviews revealed an existing literature gap in healthcare workers’ experience of happiness, health, and motivation in the context of health systems, especially in the African region [ 15 , 16 , 20 , 21 ]. Many of these studies measured these phenomena quantitatively, and hitherto regarded as more objective and reliable because of the numeric data [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation